A qualitative study of performance management systems- comparison between the performance appraisal and performance management systems in Indian textile industry - Suman, Amitabh (2019)
This research study was conducted to find out the comparison between the performance appraisal and performance management system in Indian textile industry. The objectives of the study was to find out the various appraisal systems, training, reward & incentive schemes and career development programs undertaken by the various textile companies. Moreover, the research also focus on to find out the relationship between the supervisor and their subordinates; as the textile industry which is labour intense; hence the relationship is very critical for the organisational success. Currently, the most of the textile companies are following the traditional performance appraisal method such as using checklist in order to evaluate their workers performance.